Highly expressed genes in human high grade gliomas: immunohistochemical analysis of data from the Human Protein Atlas - Michael A. Meyer (MDPI AG, 2014)
Gene expression within human glioblastomas were analyzed from data on 20,083 genes entered into the on-line Human Protein Atlas. In selecting genes that are strongly expressed within normal human brain tissue, 58 genes were identified from a search of the 20,083 entries that were rated as showing 90% or greater intensity of expression within normal brain tissues. Of these 58, a subset of 48 genes was identified that not only had expression data for human glioblastomas but also for the human glioblastoma cell line U-251. Four of these 48 selected genes were found to be strongly expressed within the cytoplasm when assessed by both histologic sampling of high grade glioma patient cases as well as U-251 glioblastoma cell line immunofluoresence analysis. These four human genes are: AGBL2 (ATP/GTP binding protein-like 2), BLOC1S6 (biogenesis of lysosomal organelles complex-1, subunit 6), MAP1A (microtubule-associated protein 1A) and ZSWIM5 (zinc finger, SWIM-type containing 5, also known as KIAA1511). Further research is advocated to investigate the role of ZSWIM5 and AGBL2 in glioma cell biology.